Risk and Protective Factors for HIV Self-disclosure among Poor African-American Women Living with HIV/AIDS. (4th March 2015) - Polansky, Marcia; Teti, Michelle; Chengappa, Roshni; Aaron, Erika
<x xml:space="preserve">Abstract</x> African-American women with HIV are among the fastest growing populations with HIV. The psychosocial factors and beliefs/attitudes associated with disclosure and other un-safe sex practices are not fully understood in this population. A total of 158 HIV-positive women receiving primary care in an HIV clinic in Philadelphia who enrolled in a safe-sex intervention, completed a baseline questionnaire on their sexual activities with male partners and psychosocial factors that were potential protective/risk factors for unsafe sex. Women who were emotionally close and monogamous with their partner were most likely to disclose their HIV status and least likely to worry they had infected their partner. Women who were non-monogamous and who did not have an emotional connection to any of their partners were least likely to self-disclose. Partners were more likely to know each other's status when the woman felt she had a responsibility to talk about the importance of staying HIV-negative.